Fear and Avoidance of Movement in People with Chronic Pain: Psychometric Properties of the 11-Item Tampa Scale for Kinesiophobia (TSK-11) - Hapidou, Eleni G. (University of Toronto Press Incorporated, 2012)
Purpose: To determine the psychometric properties of the 11-item Tampa Scale for Kinesiophobia (TSK-11) in patients with heterogeneous chronic pain. Methods: The study evaluated test–retest reliability (intra-class correlation coefficient), cross-sectional convergent construct validity (Pearson product–moment correlation between TSK-11 and the Pain Catastrophizing Scale [PCS] scores at admission), and sensitivity to change of the TSK-11 (area under the receiver operating characteristic [ROC] curve) in patients (n=74) with heterogeneous chronic pain. We used two data sets (retrospective, n=56; prospective, n=18). All patients attended the 4-week interdisciplinary chronic pain management programme at Chedoke Hospital, Hamilton Health Sciences, Hamilton, Ontario. Results: The test–retest reliability of the TSK-11 was 0.81 (95% CI, 0.58–0.93), the standard error of measurement was 2.41 (90% CI, 1.47–2.49), and the minimal detectible change score was 5.6. The correlation between TSK-11 and PCS at admission was 0.60 (95% CI, 0.43–0.73). The area under the ROC curve was 0.73 (95% CI, 0.57–0.88). Conclusions: The study results provide evidence for the test–retest reliability, cross-sectional convergent construct validity, and sensitivity to change of the TSK-11 in a population with heterogeneous chronic pain.